INTRALABORATORY VALIDATION OF AN ANALYTICAL METHODOLOGY BY UV/VIS SPECTROMETRY IN ORDER TO EVALUATE THE OCULAR IRRITANT POTENTIAL OF TENSOACTIVES IN RED BLOOD CELLS - LEGUIZAMÓN, Luz Adriana; HERRERA, Ever Andrés; MARTÍNEZ, Jorge Ariel; LOZANO, María C. (Vitae, 2011)
Red blood cell assay (RBC) intralaboratory validation was presented, specifically for linearity, repeatability and intermediate precision. RBC is an in vitro methodology employed for ocular irritation evaluation measuring surfactants adverse effects on cell membranes and proteins and is an alternative for Draize ocular test. Free hemoglobin after red blood cell lysis was determined through spectrometry at 577 nm in order to estimate medium hemolytic concentration (HC50) indicating cell damage by surfactant. Also hemoglobin denaturation induced by high concentrations of surfactants was considered measuring denaturation index (DI) through absorbance ratio at 542 and 577 determinations. HC50 / DI is an indicator of the dodecylsulphate (SDS) irritant potential, surfactant used in order to validate this assay. Parameters previously mentioned were validated and we present an easy and reliable alternative methodology for animal experimentation to assess surfactants ocular irritation for SDS.